Constructing coarse-grained skyrmion potentials from experimental data with Iterative Boltzmann Inversion - Ge, Yuqing; Rothoerl, Jan; Brems, Maarten A.; Kerber, Nico; Gruber, Raphael; Dohi, Takaaki; Klaeui, Mathias; Virnau, Peter (Communications Physics, 2023)
In an effort to understand skyrmion behavior on a coarse-grained level, skyrmions are often described as 2D quasiparticles evolving according to the Thiele equation. Interaction potentials are the key missing parameters for predictive modeling of experiments. Here, the Iterative Boltzmann Inversion technique commonly used in soft matter simulations is applied to construct potentials for skyrmion-skyrmion and skyrmion-magnetic material boundary interactions from a single experimental measurement without any prior assumptions of the potential form. It is found that the two interactions are purely repulsive and can be described by an exponential function for micrometer-sized skyrmions in a ferromagnetic thin film multilayer stack. This captures the physics on experimental length and time scales that are of interest for most skyrmion applications and typically inaccessible to atomistic or micromagnetic simulations.
CRIS-Team Scopus Importer:2023-03-27